Accumulation of heavy metals (Cu, Zn, Ni, Cr, Pb, Cd) in tissues of perch (Perca fluviatilis L.) and roach Rutilus rutilus (L.) under experimental conditions - Idzelis, Raimondas Leopoldas; Kesminas, Vytautas; Svecevičius, Gintaras; Misius, Vaidas (Journal of Environmental Engineering and Landscape Management, 2008)
The paper analyses the effects of heavy metals on freshwater fishes. From the point of view of pollution caused by heavy metals, the condition of ecosystems in Lithuania is yet less affected by heavy metals compared to that the world over. Fishes accumulate heavy metals selectively. Fishes mostly accumulate Pb, Cr, Cd. Our experiments showed that MPC (Maximum Permitted Concentration) (0.2 mg/kg) of lead was exceeded 1.6 time in the muscles of perch, and 1.4 time – in the muscles of roach. The MPC (0.05 mg/kg) of cadmium was exceeded 1.2 time in the muscles of perch and roach. It was determined that perch accumulate heavy metals more intensively than roach. Heavy metals accumulate in fishes: liver > muscle> gills. As heavy metals are considered to be one of the most harmful water pollutants, there is a great need for a constant ecological monitoring and reduction of their amounts released into the environment. According to long‐term research data, the MPC in fishes is exceeded only slightly. This confirms a good condition of aquatic ecosystems in Lithuania. Article in Lithuanian. Sunkiųjų metalų (Cu, Zn, Ni, Cr, Pb, Cd) kaupimasis ešerio Perca fluviatilis L. ir kuojos Rutilus rutilus (L.) audiniuose eksperimento sąlygomis Santrauka. Įvertintas sunkiųjų metalų pasiskirstymas gėlavandenių žuvų audiniuose monitoringiniuose vandens telkiniuose, taip pat ir kuojų bei ešerių, paveiktų sunkiųjų metalų didžiausiomis leidžiamosiomis koncentracijomis (DLK), audiniuose. Eksperimentiniai tyrimai atlikti su Cu, Zn, Ni, Cr, Pb, Cd, kurių kiekvienas pasižymi kancerogeniniu mutageniniu poveikiu. Nustatyta, kad švino DLK (0,2 mg/kg) buvo viršyta ešerių raumenyse 1,6 karto, o kuojų – 1,4 karto. Kadmio DLK (0,05 mg/kg) ešerių ir kuojų raumenyse buvo viršyta apie 1,2 karto. Taip pat nustatyta, kad ešeriai sunkiuosius metalus kaupia intensyviau nei kuojos. Eksperimentiniai duomenys sutampa su sunkiųjų metalų tyrimų monitoringiniuose vandens telkiniuose duomenimis. Žuvų audiniuose Pb ir Cd koncentracijos yra didžiausios ir dažnai viršija Lietuvos higienos normoje nurodytąją DLK. Tokie rezultatai įpareigoja nuolat kontroliuoti sunkiųjų metalų kiekį žuvyse. Rezultatai pateikiami sunkiųjų metalų sklaidos pasiskirstymo grafikuose. Reikšminiai žodžiai: žuvys, toksiškumas, mitybinė grandis, eksperimentiniai tyrimai, higienos norma. Аккумуляция тяжелых металлов (Cu, Zn, Ni, Cr, Pb, Cd) в тканях окуня Perca fluviatilis L. и плотвы Rutillus rutillus L. в экспериментальных условиях Резюме. Представлены данные по распределению тяжелых металлов в тканях пресноводных рыб в мониторинговых водоемах, а также результаты, полученные путем воздействия тяжелых металлов в предельно допустимых концентрациях (ПДК) на окуня и плотву. В экспериментальных исследованиях применялись металлы Cu, Zn, Ni, Cr, Pb, Cd, оказывающие на живые организмы воздействие мутагенного и канцерогенного характера. Установлено, что концентрация Cd в тканях окуня превышала ПДК (0,2 мг/кг) в 1,6 раза, а в тканях плотвы – в 1,4 раза. Концентрация Cd в тканях тех же рыб превышала ПДК (0,05 мг/кг) примерно в 1,2 раза. Также установлено, что окунь аккумулирует тяжелые металлы интенсивнее плотвы. Экспериментальные данные совпадают с данными, полученными в мониторинговых водоемах. Установлено также, что концентрация Pb и Cd в тканях рыб зачастую превышает ПДК. Полученные результаты обязывают постоянно контролировать уровень тяжелых металлов в тканях рыб. Ключевые слова: рыбы, тяжелые металлы, пищевая цепь, концентрация, аккумуляция. First Published Online: 14 Oct 2010